The Application of Template Matching Algorithm to Improve Accuracy of Plate Number Recognition - R Moch Dysa Satria Anggara; Aradea; Rianto (Jurnal Rekayasa Sistem & Industri, 2022)
Pattern Recognition is a part research of Image Processing. In term implementation of Pattern Recognitionused for variety research needs such as Identify Transportation License Plate Number. Identifying licenseplate number is one process to reduce crime, accident, and support related agencies to process informationtraffic data. Taking picture of license plate number by camera create image that can be processed by OpticalCharacter Recognition (OCR). OCR is conversion process of picture that contain alphabet and numericobject into ASCII character. In creating of OCR, there’s many kind of algorithm, we used TemplateMatching algorithm as main research. Process of Template Matching algorithm is fitting all part of picturetaken by camera with image that has been processed into Template Data. However like another algorithm,this algorithm had a deficiency about accuracy and time to recognition process. To create and enhance ofaccuracy in Template Matching algorithm, we create 3 scenarios to take a picture for compare the result ofaccuracy and time to OCR process also comparing Template Matching algorithm with Learning VectorQuantization (LVQ) as accuracy comparison method. Based on result of Template Matching algorithm had84% accuracy and 0,942 Milliseconds to process OCR.